Acoustic and Perceptual Effects of Left–Right Laryngeal Asymmetries Based on Computational Modeling - Samlan, Robin A. (J Speech Lang Hear Res, 2014)
PURPOSE: Computational modeling was used to examine the consequences of 5 different laryngeal asymmetries on acoustic and perceptual measures of vocal function. METHOD: A kinematic vocal fold model was used to impose 5 laryngeal asymmetries: adduction, edge bulging, nodal point ratio, amplitude of vibration, and starting phase. Thirty /a/ and /I/ vowels were generated for each asymmetry and analyzed acoustically using cepstral peak prominence (CPP), harmonics-to-noise ratio (HNR), and 3 measures of spectral slope (H1*-H2*, B0-B1, and B0-B2). Twenty listeners rated voice quality for a subset of the productions. RESULTS: Increasingly asymmetric adduction, bulging, and nodal point ratio explained significant variance in perceptual rating (R(2) = .05, p < .001). The same factors resulted in generally decreasing CPP, HNR, and B0-B2 and in increasing B0-B1. Of the acoustic measures, only CPP explained significant variance in perceived quality (R(2) = .14, p < .001). Increasingly asymmetric amplitude of vibration or starting phase minimally altered vocal function or voice quality. CONCLUSION: Asymmetries of adduction, bulging, and nodal point ratio drove acoustic measures and perception in the current study, whereas asymmetric amplitude of vibration and starting phase demonstrated minimal influence on the acoustic signal or voice quality.